(untitled) (Al-Qamar, 2023)
The early S rah-writers recorded the biography of the Holy Prophet (peace be upon him) in the historical annals and Hadith collections but gradually S rah-writing developed as an independent discipline to elaborate the various aspects of the life of the Holy Prophet. However, a significant change has been witnessed both in S rah writing and its interpretation in the contemporary period. Thus, multiple methods and approaches are applied to present an authentic biography of the Prophet along with its various social, political, and religious aspects. The method of Qur’anic S rah-writing was introduced to record an authentic biography. Thus, the trend of Qur’anic S rah writing emerged and some an eminent scholars attempted to illustrate all aspects of the life of Holy Prophet as recorded in the Qur’an. The present paper aims to study ’Asr-al-Nabi of a well-known S rah-writer ’Izzat Darwazah who attempted to illustrate the society of the Prophetic period based on Qur’anic studies. An analytical study of the book concludes that various aspects of the society are present on Qur’anic studies and the author has substantially achieved his objectives through the application of his methodology.